Prevalence and factors associated with caesarean delivery in Nepal: evidence from a nationally representative sample - Das, Pranta; Samad, Nandeeta; Sapkota, Ashmita; Al-Banna, Hassan; A. Rahman, Nor Azlina; Ahmad, Rahnuma; Haque, Mainul; Godman, Brian (Springer Nature, 2021)
Background: Caesarian sections (CS) are life-saving management for a pregnant mother and fetus subject to obstetric complications. The World Health Organization (WHO) expected CS rates not to exceed 10 to 15 per 100 live births in any country. This study aimed to assess the prevalence of CS and its associated factors from the 2016 Nepal Demographic and Health Survey (NDHS), building on previous studies mentioned in detail in the latter part of the paper. Methods: This study analyzed the secondary data from the 2016 Nepal Demographic and Health Survey (NDHS), conducted from June 19, 2016, to January 31, 2017. The survey is undertaken every five years; consequently, the data capture the information in the previous five years from the data collection period. We used the 2016 NDHS, which is implemented by the new Enumeration Area (EA) under the support of the Ministry of Health (MOH) and funded by the U.S. Agency for International Development (USAID). In the rural areas, the sample is stratified and selected in two stages. In the first stage, wards are selected as the primary sampling units (PSU), with households subsequently chosen from the PSUs. In the urban areas, the sample is nominated in three stages. In the first stage, wards are selected as PSUs; in the second stage, one EA is chosen from each PSU, and finally, households are selected from the EAs. Then data were collected from the women in the reproductive age group within the selected households. Results: The prevalence of CS in Nepal conforms to the WHO standard with 7.8, 7.5, and 8.1 per 100 deliveries, or 9.8, 8.9, and 9.1 per women’s last births in the previous one, three, and five years, respectively. Older mothers of 30 years old or more, having high incomes, being overweight and obese, using the internet, ante-natal care (ANC) visits of more than four times, ANC by doctors, twin delivery, and having babies of 4 kg or more, had higher odds for a CS while having two or more children seemed to be protective towards CS. Conclusion: These findings can be used to update health policies surrounding CS delivery to limit unnecessary CS and ensure better health as CS is not without complications.